THE ROLE OF PARENTAL SUPERVISION IN THE IMPLEMENTATION OF ONLINE LEARNING - Lestari, Ika; Nafiah, Maratun; Putri, Alifia Rozalna (PARAMETER: Jurnal Pendidikan Universitas Negeri Jakarta, 2021)
During the Covid-19 pandemic, many countries have implemented online learning. This study provides an overview of how the role of parental supervision in the implementation of online learning. This research uses descriptive method by distributing questionnaires using google form. The sample criteria are parents aged 30-45, the data taken from parents are parents who have school children and who live in Bogor, Indonesia. With a sample of 50 people. The questionnaire was distributed online via the WhatsApp application. The results showed that there were 50 respondents with a percentage of 67,14% and it can be concluded that the role of parental supervision in the implementation of online learning is in the medium category.